The impact of China’s new Environmental Protection Law on corporate environmental investments - Liu, Weiming; Qiu, Yating; Jia, Lijiang; Wu, You; Zhou, Qingmei (Frontiers in Energy Research, 2023)
The role of environmental regulation that can promote green technology innovation as well as pollution reduction effect is widely recognized. However, the effect of such regulation on corporate environmental investment has received little research attention. This paper utilizes corporate data from non-financial listed companies in Shanghai and Shenzhen A-shares spanning from 2007 to 2018. By adopting a double-difference model, it explores the incentive role and internal mechanism of the new Environmental Protection Law (EPL), implemented in 2015, as an environmental regulation on the environmental protection investment of enterprises, taking the new EPL's enactment as a quasi-natural experiment. The study revealed a noteworthy and positive impact on motivation, which remained consistent even after various robustness tests. Additionally, the impact of incentives varied depending on the level of competition within the industry, financial constraints, and ownership type of the enterprises. Investigating the mechanism, it has been discovered that the incentive effect advances environmental investment of firms through diminishing agency costs, enriching the quality of environmental information disclosure, and facilitating government subsidies to enterprises. This study not only verifies from the factual empirical level that environmental regulation policies can promote corporate environmental investment, but also provides important evidence support to a certain extent that the implementation of the new EPL can promote enterprises' environmental governance behaviors. It is of positive significance in promoting the establishment of reasonable environmental regulatory measures, improving the enthusiasm of corporate environmental investment, and guiding the healthy and sustainable development of the social economy and the environment.